2015
DOI: 10.24059/olj.v19i4.570
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Orientation leads to Improved Success in Online Courses

Abstract: A team of instructional designers, educators, and the School of Liberal Arts (SLA) academic program coordinator from a nonprofit online college, collaborated on producing short voice-over videos with interactive elements that address the most common technology frustrations of beginning students. These videos were inserted into the "Start Here" page of the pilot study courses. Courses were selected that had a higher than average withdrawal rate and that also tended to have a broad grade distribution for student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 4 publications
1
20
0
1
Order By: Relevance
“…Fricker reported that 19 of the 20 students completed the course with a C or better and credited the support provided by the teaching assistant. Taylor et al (2015) investigated the influence of a video course orientation tutorial on online course completion rates. Their results showed significant improvement in grades and reduction in withdrawals for only some of the courses.…”
Section: Example Of Greater Detail Per Studymentioning
confidence: 99%
“…Fricker reported that 19 of the 20 students completed the course with a C or better and credited the support provided by the teaching assistant. Taylor et al (2015) investigated the influence of a video course orientation tutorial on online course completion rates. Their results showed significant improvement in grades and reduction in withdrawals for only some of the courses.…”
Section: Example Of Greater Detail Per Studymentioning
confidence: 99%
“…While online students agree that an orientation prior to the start of a course or program is important (Bozarth et al, 2004; Cho & Heron, 2015; Nash, 2005) and that student satisfaction and experience with an online orientation experience positively influence a student’s academic self-efficacy (Abdous, 2019; Brewer & Yucedag-Ozcan, 2013; Kanuka & Jugdev, 2006), it is also critical to remember that online students are diverse and, therefore, orientation programs need to be tailored for the target group of students (Wozniak et al, 2007). Participation in an orientation session has been shown to be associated with readiness to learn (Liu, 2019), successful completion of online courses (Ali & Leeds, 2009; Bawa, 2016; Russo-Gleicher, 2014; Taylor et al, 2015), and higher course grades (Bellantuono, 2020; Taylor et al, 2015; Wojciechowski & Palmer, 2005).…”
Section: Role Of Student Orientation Programsmentioning
confidence: 99%
“…However, many students-particularly those in their first term-may not understand their own academic strengths and weaknesses, and whether or how they should access available supports. Faculty can help students develop this understanding by serving as a mentor, helping them define specific steps toward achieving academic goals, sharing effective time-management strategies, and helping them develop an awareness of and willingness to utilize different avenues of academic support (Coon & Walker, 2013;Flynn, 2016;Kot, 2014;Taylor et al, 2015;Zie & Huang, 2014).…”
Section: Academic Supportmentioning
confidence: 99%
“…Crosling, Heagney, and Thomas (2009) found that an orientation class at the start of a student's college experience increased engagement by helping them grasp the most important elements of online preparedness. Taylor et al (2015) developed an orientation for first-year students with a combination of multimedia resources. Hendricks and Bailey (2014) asserted that online students must be technologically prepared to overcome the variety of multimedia content in online classes.…”
Section: Orientation To the Classroommentioning
confidence: 99%